REPERFUSION ARRHYTHMIAS IN ACUTE MYOCARDIAL INFARCTION - B.F MUKHAMEDOVA; A.K.KOIROV; D.E ABDUJABBOROVA; A.A.AZIMOV (Scholar Express Journals, 2023)
Reperfusion arrhythmias (RA) are quite a common complication of procedures aimed at restoration of coronary blood flow (percutaneous coronary interventions (PCI), thrombolysis, and aortocoronary bypass grafting). Known risk factors for RA are infarct size, duration and severity of ischemia, reperfusion rate, heart rate, extracellular potassium concentration, and the presence of congestive heart failure or left ventricular hypertrophy. Treatment of RA should be aimed primarily at improving the microcirculation of the reperfusion zone by using various groups of drugs, including direct anticoagulants, beta-blockers, and ACE inhibitors. The class III antiarrhythmic drugs, cardioversion, and radiofrequency ablation are used to eliminate arrhythmias.
Keywords: reperfusion; myocardial infarction; arrhythmia; endothelial dysfunction